2021
DOI: 10.3389/fimmu.2020.615317
|View full text |Cite
|
Sign up to set email alerts
|

LAG3’s Enigmatic Mechanism of Action

Abstract: LAG3 is an important immune checkpoint with relevance in cancer, infectious disease and autoimmunity. However, despite LAG3’s role in immune exhaustion and the great potential of LAG3 inhibition as treatment, much remains unknown about its biology, particularly its mechanism of action. This review describes the knowns, unknowns and controversies surrounding LAG3. This includes examination of how LAG3 is regulated transcriptionally and post-translationally by endocytosis and proteolytic cleavage. We also discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 57 publications
4
107
0
Order By: Relevance
“…LAG-3 binds with major histocompatibility complex class II (MHC II) with a higher affinity than CD4+ [ 27 ]. Moreover, LAG-3 can bind with the LSECtin, a member of the C-type lectin receptor superfamily, typically exposed on tumor cell membranes, and with the fibrinogen like protein 1 (FGL-1), which is part of the fibrinogen protein superfamily [ 28 ]. Several trials have reported that LAG-3 regulates inhibitory effect on T cells synergizing with the PD-1/PD-L1 axis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAG-3 binds with major histocompatibility complex class II (MHC II) with a higher affinity than CD4+ [ 27 ]. Moreover, LAG-3 can bind with the LSECtin, a member of the C-type lectin receptor superfamily, typically exposed on tumor cell membranes, and with the fibrinogen like protein 1 (FGL-1), which is part of the fibrinogen protein superfamily [ 28 ]. Several trials have reported that LAG-3 regulates inhibitory effect on T cells synergizing with the PD-1/PD-L1 axis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAG-3 is, along with PD-1/PD-L1 and CTLA-4, a promising target in cancer immunotherapy, since it plays a pivotal role in anti-tumor immunity [ 42 ]. LAG-3 blockade, alone or in combination with other ICBs, has demonstrated promising results in clinical trials [ 17 , 19 , 42 , 43 , 44 ]. Yet, little is known about the mechanisms of action underlying LAG-3 blockade in cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAG-3 blockade, alone or in combination with other ICBs, has demonstrated promising results in clinical trials [ 17 , 19 , 42 , 43 , 44 ]. Yet, little is known about the mechanisms of action underlying LAG-3 blockade in cancer [ 43 ]. Relatlimab, an anti-LAG-3 blocking mAb, is currently one of the most advanced mAbs in clinical trials targeting solid tumors and hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte activation gene-3 (LAG-3), also known as CD223, is expressed on multiple cell types including conventional T cells, NK cells, B cells [ 109 ], and unconventional T cells [ 109 , 110 , 111 ]. LAG-3 is an IgSF transmembrane protein with four extracellular domains that have similar folding patterns with CD4 in both humans and mice, indicating that LAG-3 can also bind to MHC-II, although at a different site than CD4 [ 112 ].…”
Section: Lag-3mentioning
confidence: 99%
“…LAG-3 is an IgSF transmembrane protein with four extracellular domains that have similar folding patterns with CD4 in both humans and mice, indicating that LAG-3 can also bind to MHC-II, although at a different site than CD4 [ 112 ]. However, the intracellular regions of LAG-3 and CD4 do not have similarities [ 109 , 112 ]. Other LAG-3 ligands include FGL-1 (Fibrinogen-like Protein 1), Gal-3 (Galectin-3), and LSECtin (Lymph Node Sinusoidal Endothelial Cell C-type Lectin) and each has been shown to induce LAG-3-mediated inhibition of T cell activation [ 113 , 114 , 115 ], supporting the idea that LAG-3 could exert its inhibitory action independently of CD4.…”
Section: Lag-3mentioning
confidence: 99%